Bioinformatics analysis of COMMD family in pan-cancer reveals potential biomarkers and therapeutic targets - Sihan Wang; Jinglei Cheng; Zhiya Hu; Hongjun Zhao; Lifen Ye; Jingyong Li; Youyuan Deng; Ye He (Scientific Reports)
Abstract The copper-metabolism Murr1 domain (COMMD) protein family plays an essential role in tumours and the immune system. However, the multi-omics characterisation of COMMD family genes and their role in tumour patients has yet to be explored. We collected data from 33 types of cancer and conducted a comprehensive analysis of the expression abnormalities, diagnostic and prognostic roles, subcellular localisation, pathway enrichment, immune microenvironment and immune checkpoint associations of COMMD family genes in these diseases. We also predicted patient responses to immunotherapy using ICIs. Finally, we confirmed the role of COMMD7 in ccRCC and bladder cancer through in vivo and in vitro experiments. We found differential expression and diagnostic biomarker value of the COMMD family of proteins in pan-cancer, and also found that they play a key role in the tumour microenvironment. COMMD proteins are closely related to common immune checkpoints, TMBs and MSIs, and COMMD family proteins can predict immunotherapy response in patients with various cancers. Finally, knockdown of COMMD7 was found to inhibit the progression of ccRCC and bladder cancer cells, as verified by in vivo and in vitro experiments. Our study highlights the great potential of COMMDs as prognostic and immunotherapeutic response biomarkers, which could pave the way for further research into tumour infiltration mechanisms and the therapeutic potential of COMMDs in cancer.